Lack of association between three vascular endothelial growth factor gene polymorphisms and systemic sclerosis: results from a multicenter EUSTAR study of European Caucasian patients. Issue 2 (1st June 2006) - Allanore, Y; Borderie, D; Airo, P; Guiducci, S; Czirják, L; Nasonov, E L; Riemekasten, G; Caramaschi, P; Majdan, M; Krasowska, D; Friedl, E; Lemarechal, H; et al.
Abstract : Introduction: Systemic sclerosis (SSc) is characterised by disturbed vessel morphology and an overproduction of vascular endothelial growth factor (VEGF). The VEGF gene located on chromosome 6p21.3 has several polymorphisms. Objective: To test the hypothesis that disturbed angiogenesis may be related to the genetic background of the VEGF gene. Materials and methods: EUSTAR centres included European Caucasian patients with SSc and matched controls with osteoarthritis. The VEGF gene was genotyped by polymerase chain reaction, followed by restriction enzyme analysis. The 634 C/T and 936 C/G mutations and an 18-base pair insertion/deletion at −2549 of the VEGF promoter region were tested. Results: 416 patients with SSc and 249 controls were included in the study population. Of the patients with SSc, 42% had a diffuse cutaneous subtype, 16% had increased pulmonary arterial pressure and 61% had decreased carbon monoxide diffusion capacity. The genotype frequencies in the patients with SSc and in controls were in Hardy–Weinberg equilibrium. The allele and genotype frequencies of the polymorphisms did not differ between patients with SSc and controls. No association was found between these polymorphisms and disease phenotypes. Conclusion: This study shows that there is no association between the three selected functional VEGF polymorphisms and SSc.